Modeling customer satisfaction in cellular phone services - Muhammad Mohsin, Butt; Ernest Cyril, de Run (Jurnal Kemanusiaan, 2009)
Low tariffs, wider coverage and decent quality keep Pakistani cellular phone market growth at an alarming pace. Despite highest growth rate in the region, the lucrative Pakistani market is not free from challenges. The intensified competition is depicting a pattern of customer churn while the companies are still enjoying growth. This creates serious challenges for organizations in managing their existing customer while striving for growth. The common answer to such challenges is retaining customers through satisfaction. This research aims at answering what are the factors contributing towards customer satisfaction in Pakistani mobile cellular services? A typical two-stage survey was conducted. A qualitative research was conducted in first stage to collect factors, which contribute towards the customer satisfaction of a typical Pakistani cellular phone user. It was followed with a questionnaire to gather quantitative data for further analysis using conformity factor analysis. The results confirmed a multidimensional construct of customer satisfaction in Pakistani cellular phone communication sector. The findings suggest that customer satisfaction of cellular phone users in Pakistan constitute of four factors including price, transmission quality, usage ease and service support. This is in line with the previous research exploring the issue in other countries.